Optical and electron microscopy and immunocytochemistry in the examination of transgenic expression: consultant final report IICA/EMBRAPA-PROCENSUL II - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
24 páginas.